Self-decoupling sensor and preparation method and application thereof

By stacking the resistance sensing module and the capacitor sensing module, the superposition structure of the flexible base layer and the conductive nano -fiber felt, the dual -function sensing capacity of the self -decoupling is realized, and the accurate sensor point separation and signal interference of the sensor should be solved. The problem achieves the sensory effect of high precision and anti -interference.

CN119354242APending Publication Date: 2025-01-24ZHEJIANG SCI-TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411360721.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, the precise strain sensing points of the sensor are separated from each other, limiting the accuracy of the sensing position, and the output sensing signals caused by pressure and stretching are easily disturbed, making it difficult to accurately determine the type and value of the correct stimulus.

Method used

The stacked resistance sensing module and capacitive sensing module are used to achieve the dual -functional sensing capacity of self -decoupling through the superposition structure of flexible base layer and conductive nano -fiber felt. Conductive nano -fiber felt obtained through nano -cellulose and polyvinyl alcohol static spinning, and attached polypyle on the surface as conductive substances.

Benefits of technology

A self -dissolving sensor with excellent anti -interference performance can be independently sensing and stretching independently, eliminating interference between the two, and improving the accuracy of the sensing position and the accuracy of the signal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354242A_ABST
    Figure CN119354242A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sensors, and particularly relates to a self-decoupling sensor and a preparation method and application thereof. The self-decoupling sensor comprises a resistance sensing module and a capacitance sensing module which are stacked. The resistance sensing module comprises a flexible substrate layer, a first conductive nanofiber felt and a flexible substrate layer which are stacked in sequence; wherein the first conductive nanofiber felt is of a resistance sensing structure; the capacitance sensing module comprises a flexible substrate layer, a second conductive nanofiber felt and a flexible substrate layer which are stacked in sequence; wherein the second conductive nanofiber felt is of a capacitance sensing structure; wherein one flexible substrate layer of the resistance sensing module is compounded with one flexible substrate layer of the resistance sensing module. The multi-module sensor is excellent in anti-interference performance and has a self-decoupling function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensors, and in particular relates to a self-decoupling sensor and a preparation method and application thereof. Background Art

[0002] With the needs of social development and the expansion of robot application fields, people's requirements for intelligent robots are getting higher and higher. The environment in which intelligent robots are located is often unknown and unpredictable. In the process of studying intelligent robots, technologies such as intelligent sensing are mainly involved. When an intelligent robot grasps an object with its hands, its perception system of the object is not limited to the gravity and size of the object. On the contrary, it shows the efficient coupling of the object's pressure and stretch sensing functions to the hand. Therefore, the realization of integrated pressure and stretch sensing in the field of intelligent sensing has attracted the attention of more and more researchers. It can be attached to the surface of the device like clothes, allowing the intelligent robot to perceive information such as the weight and volume of the object. Therefore, the field of intelligent robots is in urgent need of developing a sensing material with simple preparation, low cost and excellent sensing performance.

[0003] Nanocellulose CNC has been initially commercialized in the fields of fully biodegradable plastics, drug sustained-release carriers, moisturizing masks, optical or anti-counterfeiting materials, and flexible display devices due to its advantages of being stronger than ordinary steel, transparent, low-density, and rich in hydrophilic groups. Houyong Yu et al. published an article titled "Self-healable Conductive Nanocellulose Nanocomposites for Biocompatible Electronic Skin Sensor System" in the journal ACS applied materials & interfaces. It introduces CNC as a reinforcing material to prepare sensors, which has great potential in the fields of motion monitoring, smart robot sensor skin, etc.

[0004] In addition, the patent document with publication number CN104105656A discloses a substrate and a sensor element with different materials and different thermal expansion coefficients, the sensor element and the substrate each have generally flat surfaces arranged substantially parallel to each other, the sensor also includes a spacer, and the sensor device is not an integrated unit. Under this design, the precise sensing points of strain are separated from each other, which limits the accuracy of the sensing position, and the output sensing signals caused by pressure and stretching are inevitably disturbed. Under the same output, it is very difficult or complicated to accurately determine the type and value of the correct stimulus. Therefore, the key is how to enable a sensing material to have a fully decoupled dual-function sensing capability to achieve the wide application of intelligent sensing technology; in this way, it can be used in intelligent robots such as hands, improve mechanical properties, improve responsiveness, and sensing feedback capabilities, and can be vigorously promoted. Summary of the invention

[0005] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a method that meets one or more of the above-mentioned needs.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A self-decoupling sensor comprises a stacked resistance sensing module and a capacitance sensing module;

[0008] The resistance sensing module comprises a flexible base layer, a first conductive nanofiber felt and a flexible base layer stacked in sequence; wherein the first conductive nanofiber felt is a resistance sensing structure;

[0009] The capacitive sensing module comprises a flexible base layer, a second conductive nanofiber felt and a flexible base layer stacked in sequence; wherein the second conductive nanofiber felt is a capacitive sensing structure;

[0010] Wherein, one of the flexible base layers of the resistance sensing module is compounded with one of the flexible base layers of the resistance sensing module.

[0011] As a preferred embodiment, both the first conductive nanofiber mat and the second conductive nanofiber mat are nanofiber mats with conductive materials attached.

[0012] As a preferred embodiment, the nanofiber felt is obtained by electrostatic spinning of a spinning solution consisting of nanocellulose and polyvinyl alcohol.

[0013] As a preferred embodiment, the conductive material is polypyrrole.

[0014] As a preferred solution, the flexible substrate layer is a PVA film.

[0015] The present invention also provides a method for preparing a self-decoupling sensor as described in any of the above schemes, comprising the following steps:

[0016] (1) Preparation of resistance sensor module

[0017] A nanofiber spinning solution is prepared, and electrospinning is performed on a flexible substrate layer to obtain a first nanofiber felt, and then an initiator is attached to the surface of the first nanofiber felt, and then a conductive material is vapor-phase polymerized to obtain a first conductive nanofiber felt; finally, another flexible substrate layer is compounded on the surface of the first conductive nanofiber felt to obtain a resistance sensing module;

[0018] (2) Preparation of capacitive sensing module

[0019] A nanofiber spinning solution is prepared, a paper template with a capacitive sensing structure is pasted on a flexible substrate layer, and electrostatic spinning is performed to obtain a second nanofiber felt, and then an initiator is attached to the surface of the second nanofiber felt, and then a conductive material is vapor-polymerized, and the paper template is removed to obtain a second conductive nanofiber felt; finally, another flexible substrate layer is compounded on the surface of the second conductive nanofiber felt to obtain a capacitive sensing module;

[0020] (3) Preparation of self-decoupling sensor

[0021] One of the flexible substrate layers of the resistance sensing module is compounded with one of the flexible substrate layers of the resistance sensing module to obtain a self-decoupling sensor.

[0022] As a preferred embodiment, the nanofiber spinning solution is composed of nanocellulose and polyvinyl alcohol, and the solid-liquid ratio is 1g: (20-30)mL.

[0023] As a preferred embodiment, the initiator is AlCl3, FeCl3 or ammonium persulfate.

[0024] As a preferred solution, the flexible base layer is a PVA film, and the composite is bonded by water jet bonding.

[0025] The present invention also provides a self-decoupling sensor as described in any of the above schemes or a self-decoupling sensor prepared by the preparation method as described in any of the above schemes, as a sensing element of an intelligent robot.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The self-decoupling sensor of the present invention has excellent anti-interference performance and self-decoupling function;

[0028] (2) The present invention uses PVA substrate, which is widely available and easy to prepare, as raw material, and has the advantages of simple preparation process, low energy consumption, degradability, and excellent transparency and visualization of the prepared material. It has good compatibility in structure and can be used as an excellent flexible substrate;

[0029] (3) The present invention abandons the polymerization between traditional substances and adopts gas phase polymerization and technology to polymerize conductive substances;

[0030] (4) The preparation method used in the present invention is simple, the structure is innovative, the market demand is large, and the self-decoupling function has considerable social and economic benefits;

[0031] (5) The sensor of the present invention has a visualized sandwich structure and can realize a visualized conductive network. This visualized multi-module intelligent sensor with excellent strength, excellent sensing capability and excellent self-decoupling capability can be applied in the field of intelligent robots as the hand sensing skin of the robot, giving the intelligent robot a sensitive "sense of touch" and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a field emission scanning electron microscope image of the electrospun conductive nanofiber felt attached with polypyrrole according to Example 1 of the present invention;

[0033] Figure 2 This is a cross-sectional field emission scanning electron microscope FE-SEM test image of a single-layer sensor according to Example 3 of the present invention;

[0034] Figure 3 This is a mechanical test diagram of a single-layer sensor according to Example 3 of the present invention;

[0035] Figure 4 This is a test diagram of the anti-interference performance of the double-layer sensor according to Example 4 of the present invention;

[0036] Figure 5 This is a diagram illustrating the application of the decoupling capability of the double-layer sensor of Example 4 of the present invention;

[0037] Figure 6 This is a schematic diagram of the configuration of a double-layer sensor according to Embodiment 4 of the present invention.

[0038] Figure 7 This is the working mechanism and application of the double-layer sensor of Example 4 of the present invention. DETAILED DESCRIPTION

[0039] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.

[0040] The following examples and comparative examples are used for test description:

[0041] The tests were carried out at room temperature using a universal testing machine (Instron 5943, Illinois Tool Works Inc.), and all samples were placed in a specific environment (temperature: 25 (±1) °C; humidity: 50%) for 24 h to eliminate the effect of moisture content on mechanical properties;

[0042] A digital multimeter (Agilent Truevolt 34461A digital multimeter (DMM)) was used to test the real-time resistance signal change and voltage signal change of the sensor.

[0043] Embodiment 1:

[0044] Prepare CNC, and prepare a CNC dispersion with a solid-liquid ratio of 1g:50mL, and ultrasonicate for 20min; prepare a PVA solution with a solid-liquid ratio of 1g:7mL, PVA is purchased from Aladdin, put it in a water bath at 80℃ and stir (speed 35r / min) for 240min; prepare an electrospinning solution with a solid-liquid ratio of 1g:10mL; prepare an initiator ferric chloride solution with a solid-liquid ratio of 1g:6mL, where ferric chloride is purchased from Aladdin, with a molecular weight of 162.3, and stir for 30min; add the above PVA solution to the CNC dispersion, where the CNC:PVA mass ratio is 1:19, stir (speed 248r / min) for 12h; use an electrospinning device to manufacture nanofiber mats. The prepared CNC-PVA electrospinning solution is loaded into a 10mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86mm. Apply a 20kV potential to the tip of the syringe needle. An aluminum collector was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. The electrospinning was performed at a temperature of 30-35 °C and a relative humidity of 50%-60%. The rotation time of all samples was 18 h, and the syringe was rotated every 2 h to prevent CNC precipitation. The obtained CNC-PVA fiber felt was collected on aluminum foil, and the entire electrospun fiber felt with the template was removed from the aluminum foil, sprayed and soaked in ferric chloride solution for 5 min, and then placed in a culture dish to air dry naturally until there was no solvent to obtain the attached Fe 3+ The nanofiber felt is placed in a vacuum bottle and placed in an oven at 35°C for 3 hours to gas-polymerize 2 ml of a conductive substance, pyrrole monomer (Py); thus, an electrospun nanofiber felt conductive composite material with polypyrrole attached is obtained.

[0045] Embodiment 2:

[0046] Nanofiber mats were fabricated using an electrospinning device. The prepared CNC-PVA electrospinning solution was loaded into a 10 mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86 mm. A potential of 20 kV was applied to the tip of the syringe needle. A PVA film was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. Electrospinning was performed at a temperature of 30-35 °C and a relative humidity of 50%-60%. The rotation time of all samples was 18 h. The syringe was rotated every 2 h to prevent CNC precipitation. The obtained CNC-PVA fiber felt was collected on a PVA film and sprayed with ferric chloride. The material was naturally air-dried until there was no solvent. It was then placed in a vacuum bottle and placed in an oven at 35 °C for 3 h with 2 ml of a conductive substance, pyrrole monomer (Py), for vapor polymerization. It was then adhered to another layer of PVA film and pressed with a glass plate to make it flat enough to obtain a resistive sensor device.

[0047] Embodiment 3:

[0048] Nanofiber mats were fabricated using an electrospinning device. The prepared CNC-PVA electrospinning solution was loaded into a 10 mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86 mm. A potential of 20 kV was applied to the tip of the syringe needle. An aluminum collector was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. Electrospinning was performed at a temperature of 30-35 °C and a relative humidity of 50%-60%. The rotation time of all samples was 18 h. The syringe was rotated every 2 h to prevent CNC precipitation. The second layer of electrospun fiber felt was directly spun onto the paper template PVA film with a capacitive sensing structure. Ferric chloride was sprayed on the two materials. The two materials were naturally air-dried until solvent-free. Then they were placed in a vacuum bottle and 2 ml of conductive material pyrrole monomer (Py) was placed in an oven at 35 °C for 3 h. Then they were adhered to another layer of PVA film and pressed with a glass plate to make it flat enough to obtain a capacitive sensor device.

[0049] Embodiment 4:

[0050] Nanofiber mats were fabricated using an electrospinning device. The prepared CNC-PVA electrospinning solution was loaded into a 10 mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86 mm. A potential of 20 kV was applied to the tip of the syringe needle. An aluminum collector was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. Electrospinning was performed at a temperature of 30-35 °C and a relative humidity of 50%-60%. The rotation time of all samples was 18 h, and the syringe was rotated every 2 h to prevent CNC precipitation. The resistive sensor was prepared by collecting the obtained CNC-PVA fiber felt on aluminum foil and then removing it and soaking it in ferric chloride. The capacitive sensor was prepared by directly spinning the two-layer electrospun fiber felt onto the PVA film pasted with a paper template and spraying it with ferric chloride. The two materials were naturally air-dried until there was no solvent, and then placed in a vacuum bottle. 2 ml of conductive material pyrrole monomer (Py) was placed in an oven at 35°C for 3 h; it was adhered to another PVA film to form a sandwich structure, and pressed with a glass plate to make it sufficiently flat to obtain a pressure-stretch sensor device that can achieve complete decoupling. A small amount of water was sprayed on the surface of the PVA film of the two sensors and allowed to stand for a period of time to make its surface slightly sticky, and then superimposed on each other to make it sufficiently flat to obtain a pressure-stretch sensor device that can achieve complete decoupling.

[0051] like Figure 1 As shown in the field emission scanning electron microscope image of the nanofiber felt conductive composite material prepared in Example 1, the volume of the CNC rod-like structure combined with the filamentary structure material on the surface of the conductive composite material becomes larger, indicating that the CNC-PVA nanofiber felt successfully polymerizes polypyrrole and has a stable structure; Figure 2 As shown in the cross-sectional field emission scanning electron microscope (FE-SEM) test diagram of the single-layer sensor prepared in Example 3, it is shown that the cross-sectional structure of the material is stable and compactly arranged, and the conductive composite tightly wraps the fibers, effectively improving the mechanical properties and signal output of the material; Figure 3As shown, the prepared single-layer sensor has excellent structural stability, which is beneficial to its flexibility and bendability. Compared with the pure PVA-derived electrospun material PVA electrospun film (4.38MPa), the incorporation of CNC material effectively improved the mechanical properties, and the CNC-PVA electrospun film reached 7.1MPa. Compared with the single-layer PVA film, the addition of CNC-PVA electrospun nanofiber film significantly improved the tensile strength of the single-layer sensor. Compared with the pure PVA film, the maximum tensile strength of the single-layer sensor attached to the PVA film reached 61.9MPa, which may be attributed to its unique interchain "soft and hard" network structure, in which CNC and PPy are connected to PVA through hydrogen bond interactions, and PVA as a continuous phase enhances toughness and flexibility. These results indicate that the addition of CNC-PVA electrospun membrane enhances the mechanical properties of the material. As Figure 4 As shown, the sensor is placed on a tensile testing machine to detect the capacitance signal ( Figure 4 a). Under different bending and stretching strains of the palm or finger, the relative capacitance change value remains almost unchanged, indicating that the pressure sensing signal is not affected by the stretching strain range ( Figure 4 bc). When the material is stretched, the initial fluctuation rate of the relative capacitance change value is still significantly lower than the strain detection limit. Therefore, the pressure sensing function remains stable and is not affected by the stretching stimulus. In order to test the effect of pressure on the stretching performance, a pressure tester was used to apply different pressures ( Figure 4 d). The relative resistance change value remains almost constant within the pressure range of 0 to 4 kPa, indicating that the resistance sensing signal is not affected by the normal human-machine interaction pressure range. The activities of clicking the mouse with fingers and placing objects in the palm of the hand do not affect the relative resistance change value of the sensor, demonstrating the application of accurate resistance sensing under conditions such as robot performing housework, grasping and touching objects ( Figure 4 ef). The design of the dual-function sensing mode uses different sensing mechanisms, namely capacitive and resistive sensing mechanisms. This design allows the main sensing function to operate independently of other stimuli, completely decoupling the pressure and tension sensing capabilities, and realizing the development of dual-function sensors. Figure 5 As shown, the anti-interference performance test of the double-layer sensor of Example 4 is to apply the decoupled pressure-stretch sensing by grasping an actual object with the hand. The copper wires on both sides of the sensor are directly bonded to the human hand to simulate grasping the object. The object is used with fruits of different volumes and weights. The device is connected to the hand holding a pineapple with a volume of 580cm 3 , weighing 610g. They are detected by the response degree of capacitance signal and resistance signal, such as Figure 5As shown in a; when connected to the capacitive sensor, the material is subjected to a pressure of 610g, the capacitive signal remains stable, and the resistance signal has almost no response. When the hand is connected to the resistance sensor, the volume of the pineapple is 580cm 3 , the metacarpal joint needs to be bent 32° to maintain, the material tensile strain is 7%, the output resistance signal responds sensitively, while the capacitance signal has almost no response. Figure 5 As shown in b, when the hand grasps a weight of 174g, the volume is 250cm 3 When the orange is stretched, the applied pressure is monitored. The capacitance signal remains stable, and the resistance signal has almost no response. The monitored effect is stretching. Since the volume is 250cm 3 The hand joint needs to be bent 57° to maintain, at which time the material tensile strain is 9%, and the resistance signal response is sensitive to the capacitance signal and almost unresponsive; similarly, when we detect a smaller volume, the mass of the mangosteen is the same, the mass of the mangosteen is 112g, the capacitance signal of the upper capacitance sensor responds sensitively and regularly, and is not affected by the stretching stimulus; the volume of the mangosteen is about 110cm 3 , the hand joint needs to be bent 75° to maintain, the material tensile strain is 12%, which will not affect the relative capacitance change of the sensor, and the application of resistance sensing is accurate ( Figure 5 c).

[0052] Comparative Example 1:

[0053] The self-decoupling sensor capable of realizing the self-decoupling function of this comparative example is different from that of Example 1 in that the proportions of the electrospinning solutions are inconsistent.

[0054] The preparation method of the self-decoupling sensor capable of realizing the self-decoupling function of this comparative example comprises the following steps:

[0055] Prepare CNC, and prepare a CNC dispersion with a solid-liquid ratio of 1g:75mL, and ultrasonicate for 20min; prepare a PVA solution with a solid-liquid ratio of 1g:10mL, PVA is purchased from Aladdin, put it into a water bath at 80℃, and stir (speed is 35r / min) for 240min; prepare an electrospinning solution with a solid-liquid ratio of 1g:10mL; prepare an initiator ferric chloride solution with a solid-liquid ratio of 1g:6mL, where ferric chloride is purchased from Aladdin, with a molecular weight of 162.3, and stir for 30min; add the above PVA solution to the CNC dispersion, where the CNC:PVA mass ratio is 1:42, and stir (speed is 248r / min) for 12h; use an electrospinning device to manufacture nanofiber mats. The prepared CNC-PVA electrospinning solution is loaded into a 10mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86mm. Apply a 20kV potential to the tip of the syringe needle. An aluminum collector was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. The electrospinning was performed at a temperature of 30-35°C and a relative humidity of 50%-60%. The rotation time of all samples was 18 h. The syringe was rotated every 2 h to prevent CNC precipitation. The obtained CNC-PVA fiber felt was collected on aluminum foil. The entire electrospun fiber felt with the template was removed from the aluminum foil, sprayed and soaked in the ferric chloride solution prepared in step (2) for 5 min, and then placed in a culture dish to air dry naturally until there was no solvent to obtain the attached Fe 3+ The nanofiber felt is placed in a vacuum bottle and 2 ml of conductive material pyrrole monomer (Py) is placed in an oven at 35°C for 3 hours to obtain an electrospun nanofiber felt conductive composite material with polypyrrole attached. The prepared fiber felt has poor mechanical effect and is easy to break.

[0056] Comparative Example 2: The self-decoupling sensor capable of realizing the self-decoupling function in this comparative example is different from that in Example 1 in that a different material is used to replace the PVA film.

[0057] The preparation method of the self-decoupling sensor capable of realizing the self-decoupling function of this comparative example comprises the following steps:

[0058] Nanofiber mats were fabricated using an electrospinning device. The prepared CNC-PVA electrospinning solution was loaded into a 10 mL syringe equipped with an 18-gauge steel needle with an inner diameter of 0.86 mm. A potential of 20 kV was applied to the tip of the syringe needle. An aluminum collector was placed 12 cm away from the needle tip to collect the electrospun nanofibers. The mixed solution was electrospun at a constant flow rate of 750 mL / h. The rotating cylinder was set to 300 rpm in the opposite direction. Electrospinning was performed at a temperature of 30-35 °C and a relative humidity of 50%-60%. The rotation time of all samples was 18h, and the syringe was rotated every 2h to prevent CNC precipitation. The obtained CNC-PVA fiber felt was collected on aluminum foil and then removed by soaking in ferric chloride. The two-layer electrospun fiber felt was directly spun onto the PLA film pasted with a paper template and sprayed with ferric chloride. The material was naturally air-dried until solvent-free, and then placed in a vacuum bottle. 2ml of conductive material pyrrole monomer (Py) was placed in an oven at 35℃ for 3h to gas phase polymerization; that is, a conductive composite material of electrospun nanofiber felt attached with polypyrrole was obtained, which was adhered to another PLA film, pressed with a glass plate, and superimposed on each other to make it sufficiently flat. The materials were not compatible, so the superimposed structure could not be achieved.

[0059] In the above embodiment, the initiator may also be AlCl3 or ammonium persulfate, and the solid-liquid ratio of the initiator may also be 0.16g:100mL, 0.08g:100mL, 0.04g:100mL, etc.;

[0060] In the above embodiment, the visualized sandwich structure can be prepared with only the substrate

[0061] In the above embodiment, the conductive material is grown by mist polymerization instead of by air polymerization;

[0062] The self-decoupling sensor capable of realizing the self-decoupling function prepared by the above-mentioned example includes a stacked resistance sensing module and a capacitance sensing module; Figure 6 As shown on the left, the resistance sensing module includes a flexible substrate layer (i.e., a PVA substrate), a first conductive nanofiber felt, and a flexible substrate layer stacked in sequence; wherein the first conductive nanofiber felt is a resistance sensing structure; Figure 6As shown on the right, the capacitive sensing module includes a flexible substrate layer, a second conductive nanofiber felt and a flexible substrate layer stacked in sequence; wherein the second conductive nanofiber felt is a capacitive sensing structure; after being stacked on each other, the compatibility of the PVA substrate in the upper and lower stacking structures ensures focused capacitive and resistive sensing at the same point. This arrangement enables the transition from simple two-dimensional planar structures to more complex three-dimensional sensing environments. Independent pressure and stretch sensing mechanisms effectively eliminate interference between these stimuli, facilitating accurate and fully decoupled pressure-tension sensing applications. This feature allows the detection of subtle pressures on objects of different volumes, such as Figure 7 As shown, a robotic arm is used to simulate the situation when grasping an object. When the hand grasps the object, the resistance response of the object to the dual-function sensing material is mainly concentrated in the metacarpophalangeal joint, and the sensing points of pressure and stretch are also located at the same position. The bending angle of the metacarpophalangeal joint ranges from 0 to 90 degrees. The horizontal coordinate can be regarded as the metacarpophalangeal joint in the Cartesian coordinate system, and the angle between the curve and the horizontal coordinate represents the required bending angle of the finger. The angle change of the metacarpophalangeal joint when holding different objects (same volume and same mass) and its effect on the tensile strain of the sensing material. When holding objects of the same volume, the resistance of the sensor hardly changes and the signal remains stable; when holding objects of the same mass, the angle change of the metacarpophalangeal joint leads to an obvious resistance response of the sensing material.

[0063] The present invention proposes to prepare a double-layer sensing material containing cellulose nanocrystals with polyvinyl alcohol (PVA) as the base material. An initiator (such as AlCl3, FeCl3 or ammonium persulfate) can be used to polymerize a conductive monomer (such as pyrrole, Py) to the surface of CNC-PVA nanofiber felt to form a CNC-PVA-PPy conductive nanofiber felt as a conductive polymer. Then the conductive nanofiber felt is sandwiched between two layers of transparent visual PVA films to form a sandwich structure, and the PVA films between the double-layer sensors are adhered together to serve as the sensing skin of an intelligent robot for motion monitoring and signal transmission. The product has the advantages of simple preparation method, low cost, high transparency, and the ability to achieve complete decoupling of pressure and stretching. This visual intelligent sensing material with excellent strength and excellent sensing ability can be applied to the field of intelligent robots as the hand sensing skin of the robot, giving the intelligent robot a sensitive "sense of touch", and has broad application prospects.

[0064] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected within the limited range according to actual needs. The experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here. However, the content that needs to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.

[0065] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A self-decoupling sensor, characterized in that: It includes a stacked resistance sensing module and a capacitance sensing module; The resistance sensing module comprises a flexible base layer, a first conductive nanofiber felt and a flexible base layer stacked in sequence; wherein the first conductive nanofiber felt is a resistance sensing structure; The capacitive sensing module comprises a flexible base layer, a second conductive nanofiber felt and a flexible base layer stacked in sequence; wherein the second conductive nanofiber felt is a capacitive sensing structure; Wherein, one of the flexible base layers of the resistance sensing module is compounded with one of the flexible base layers of the resistance sensing module.

2. The self-decoupling sensor according to claim 1, characterized in that: The first conductive nanofiber felt and the second conductive nanofiber felt are both nanofiber felts with conductive materials attached.

3. The self-decoupling sensor according to claim 2, characterized in that: The nanofiber mat is obtained by electrostatic spinning of a spinning solution consisting of nanocellulose and polyvinyl alcohol.

4. The self-decoupling sensor according to claim 2, characterized in that: The conductive material is polypyrrole.

5. The self-decoupling sensor according to any one of claims 1 to 4, characterized in that: The flexible substrate layer is a PVA film.

6. The method for preparing a self-decoupling sensor according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of resistance sensor module A nanofiber spinning solution is prepared, and electrospinning is performed on a flexible substrate layer to obtain a first nanofiber felt, and then an initiator is attached to the surface of the first nanofiber felt, and then a conductive material is vapor-phase polymerized to obtain a first conductive nanofiber felt; finally, another flexible substrate layer is compounded on the surface of the first conductive nanofiber felt to obtain a resistance sensing module; (2) Preparation of capacitive sensing module A nanofiber spinning solution is prepared, a paper template with a capacitive sensing structure is pasted on a flexible substrate layer, and electrostatic spinning is performed to obtain a second nanofiber felt, and then an initiator is attached to the surface of the second nanofiber felt, and then a conductive material is vapor-polymerized, and the paper template is removed to obtain a second conductive nanofiber felt; finally, another flexible substrate layer is compounded on the surface of the second conductive nanofiber felt to obtain a capacitive sensing module; (3) Preparation of self-decoupling sensor One of the flexible substrate layers of the resistance sensing module is compounded with one of the flexible substrate layers of the resistance sensing module to obtain a self-decoupling sensor.

7. The method for preparing a self-decoupling sensor according to claim 6, characterized in that: The nanofiber spinning solution is composed of nanocellulose and polyvinyl alcohol, and the solid-liquid ratio is 1g: (20-30)mL.

8. The method for preparing a self-decoupling sensor according to claim 6, characterized in that: The initiator is AlCl3, FeCl3 or ammonium persulfate.

9. The method for preparing a self-decoupling sensor according to claim 6, characterized in that: The flexible base layer is a PVA film, and the composite is bonded by water spraying.

10. The self-decoupling sensor according to any one of claims 1 to 5 or the self-decoupling sensor obtained by the preparation method according to any one of claims 6 to 9, characterized in that: As a sensing element for intelligent robots.

Citation Information

Patent Citations

  • Strain decoupled sensor

    CN104105656A